Nicotine‐induced neuroplasticity in striatum is subregion‐specific and reversed by motor training on the rotarod. (10th April 2019) - Licheri, Valentina; Eckernäs, Daniel; Bergquist, Filip; Ericson, Mia; Adermark, Louise
Abstract: Nicotine is recognized as one of the most addictive drugs, which in part could be attributed to progressive neuroadaptations and rewiring of dorsal striatal circuits. Since motor‐skill learning produces neuroplasticity in the same circuits, we postulate that rotarod training could be sufficient to block nicotine‐induced rewiring and thereby prevent long‐lasting impairments of neuronal functioning. To test this hypothesis, Wistar rats were subjected to 15 days of treatment with either nicotine (0.36 mg/kg) or vehicle. After treatment, a subset of animals was trained on the rotarod. Ex vivo electrophysiology was performed 1 week after the nicotine treatment period and after up to 3 months of withdrawal to define neurophysiological transformations in circuits of the striatum and amygdala. Our data demonstrate that nicotine alters striatal neurotransmission in a distinct temporal and spatial sequence, where acute transformations are initiated in dorsomedial striatum (DMS) and nucleus accumbens (nAc) core. Following 3 months of withdrawal, synaptic plasticity in the form of endocannabinoid‐mediated long‐term depression (eCB‐LTD) is impaired in the dorsolateral striatum (DLS), and neurotransmission is altered in DLS, nAc shell, and the central nucleus of the amygdala (CeA). Training on the rotarod, performed after nicotine treatment, blocks neurophysiological transformations in striatal subregions, and prevents nicotine‐induced impairment of eCB‐LTD. These datasets suggest that nicotine‐induced rewiring of striatal circuits can be extinguished by other behaviors that induce neuroplasticity. It remains to be determined if motor‐skill training could be used to prevent escalating patterns of drug use in experienced users or facilitate the recovery from addiction. Abstract : This preclinical study shows that nicotine alters amygdalo‐striatal circuits in a distinct temporal and spatial sequence and impairs endocannabinoid signaling in a long‐lasting manner. However, intense motor‐skill training during the initial week of withdrawal completely prevents both acute and progressive neuroadaptations in the striatum. If a functional shift in amygdalo‐striatal circuits is a neurobiological underpinning of substance abuse liability, restoring neuronal function by motor‐skill training might be sufficient to suppress escalated patters of substance use.